Do you remember?... - Stępniowski, Franciszek M. (Archaeopress Archaeology, 2018)
This is a personal narrative of an acquaintanceship between Professor Jacek Lech and the author, since 1973. While not of strictly documentary value, it may recall some aspects of archaeological activities – surveys, excavations, conferences and symposia organisation, and publishing, for over forty years. Although never formally related as teacher-student, and of relatively distant specialisations (Neolithic flints vs. historical archaeology of Mesopotamia), we could cooperate for this long time quite effectively. As I may sum up today, the profit was, on my side, enormous – the discipline and style ‘doing archaeology ’ was taught to me not less substantially by this relation than by the university course, and the plethora of practices, both in the field and in later study, added to a special ‘personal’ corpus of experience, of irreplaceable and simply priceless value for, e.g., my later teaching of archaeology at the university
il. ; 29 cm